Mapping the Landscape of Sustainable Finance: A Scopus-Based Bibliometric Analysis - Bani-Khaled, S.M.; Vieira, Elisabete; Azevedo, G.; Oliveira, J. (ustainable Horizons for Business, Education, and Technology. Contributions to Environmental Sciences & Innovative Business Technology, 2024)
This study presents a comprehensive bibliometric analysis of sustainable finance literature spanning from 2013 to 2022, employing VOSviewer for visual data representation and the Scopus database for source material. By analyzing 916 articles selected through a strategic search protocol, the research identifies critical trends, seminal works, and key contributors within the field, revealing China as the foremost nation in sustainable finance research, followed by the United Kingdom and the United States. A notable surge in related publications was observed during the COVID-19 period. The findings indicate that while financial modernization can increase carbon emissions, targeted green investments and financial mechanisms may counteract this trend and promote economic growth through enhanced investment in research, innovation, and green technologies. The study's reliance on Scopus and specific keywords may impose certain limitations; however, its in-depth analysis offers valuable insights for policymakers, scholars, and industry stakeholders and underscores the importance of advancing sustainable financial practices. This work not only contributes to academic discussion but also provides a strategic direction for future research and underscores the necessity for bolstering eco-friendly investments in the finance sector.